Professional Identity Construction of an Indonesian English Teacher: A Narrative Inquiry - Dea Analisti (Language-Edu, 2021)
This study draws on life-history interview data to explore professional identity construction of an Indonesian English teacher. Nested in a narrative inquiry approach, data were obtained from the interviews with the English teacher as the participant and analyzed through a framework that identified the emergence of salient themes. The findings showed that three factors influenced the teacher’s professional identity construction: 1) professional development activities that have been experienced by the teacher, 2) inspirational people or relationships with people that supported the development of his professional identity and 3) constraints form the institutional norms that hindered his professional identity development. Moreover, embracing the teacher identity shift and adapting the constraints from the school were two ways of the participant in constructing his professional identity. The discussion indicated that his professional identity construction was supported by teacher professional development programs and positive interactions since his teaching knowledge and beliefs continuously constructed and reconstructed and it was obstructed by the constraints from the school as the institutional realities that should be perceived. In short, his journey of professional identity construction is dynamic that changes across time and place and his experiences of foreign language learning illustrate the reconstruction of the “self” or himself.